Модернізація публічної служби: зарубіжний досвід - Гудзь, Євген Володимирович; Hudz, Yevhen Volodymyrovych (Ірпінь, 2024)
Робота полягає в аналізі визначення специфіки реформування державної служби України в контексті формування національної моделі державного управління в контексті західних тенденцій модернізації державної служби

The work consists in the analysis of the determination of the specifics of the reform of the civil service of Ukraine in the context of the formation of a national model of public administration in the context of Western trends in the modernization of the civil service
Modernization of Public Service: Foreign Experience
Keywords: модернізація публічної служби; зарубіжний досвід; демократичні країни; суспільні відносини; державна служба; modernization of public service; foreign experience; democratic countries; public relations; civil service